Zapożyczenia leksykalne z języka polskiego w gwarach pskowskich i nowogrodzkich - Wójtowicz, Marian (Studia Rossica Posnaniensia, 2016)
The author analyses 273 words borrowed from Polish to the Pskov dialect and 48 words to the Novgorod dialect. The analysis comprises the stock of loanwords, periods of borrowing, ways and directions in which the words were borrowed. The majority of loanwords are words describing material culture, such as objects of everyday use, tools, clothing and people’s names. A substantial group is formed by words describing a variety of actions and abstract concepts.